Contribución a la caracterización petromineragráfica-textural-geoquímica de las unidades litológicas mineralizadas del pórfido de cobre cuajone (sur del Perú) y su posible influencia en el Work Índex y la recuperación metalúrgica - Salcedo Núñez, Carlos Alonso (2021)
The Cuajone porphyry copper-molybdenum deposit is located in the South-West of Peru, in the province of Moquegua (Torata district). It is operated by the company Southern Peru Copper Corporation and began its operations in 1976. The deposit belongs to the Metallogenetic Belt number XIII of Peru (Acosta et al., 2011). The mine has reserves of 1,883,081 Mt @ 0.503% Cu and 0.018% Mo (Cuajone Mine Geology, 2018). The operation has a plant capacity of approximately 100 kt/day of mineralized rock. The average metallurgical recovery of copper varies by lithological unit from 81.59% in the IA FIL PTK (IA porphyry with potassic-phyllic alteration) to 85.7% in the LP QS (LP porphyry with phyllic-argillic alteration). The recovery parameter is very important economically because if it was greater in 1% just in the BA PTK unit with a tonnage of 40 kt processed per day in the plant (usual for this subunit), at a copper price of 5,904.00 USD / t (average price for the last 5 years), 4.28 million dollars (USD) of extra profit will be obtained per year (calculations in section 9.1 of Annexes). This thesis aims to evaluate if the texture and mineralogy of gangue and chalcopyrite are affecting the metallurgical recovery and the Work index. The thesis makes a bibliographic review not only of the regional and local geological framework but also of the mining and metallurgy divisions. The methodology consists of: sampling; optical microscopy; X-Ray Diffraction - SWIR (Terraspec) and geochemistry (XRF, ICP-AES-MS). The discussion section deals with the following topics: Total Petromineragraphic Characterization and correlation of macroscopic-microscopic characteristics; mineralogy of fine-grained clays and phyllosilicates; maximum and average chalcopyrite grain sizes; types of chalcopyrite-opaque mineral and chalcopyrite-gangue mineral intergrowth textures; Rock Texture-Work index relationship; and latter a geometallurgical approach analysis. Finally, the present work generates a conclusion regarding the petrological classification based on geochemistry; a hypothesis of 3 factors that control the difference in recovery between the lithological units; and a recommendation is given on how to optimize these 3 factors to improve recovery and therefore economical revenue.